Effect of Palladium Nanoparticles on Photocatalytic Characteristics of N doped Titania Catalyst. Issue 6 (June 2015) - Lee, Jong-Ho; Youn, Jeong-Il; Kim, Young-Jig; Oh, Han-Jun
Abstract : To improve the photocatalytic efficiency of TiO2 nanotubular catalyst, N doped and Pd decorated titania nanotubes was successfully synthesized via anodizing, hydrazine hydrate treatment and photoreduction of Pd ions. The small Pd nanoparticles were precipitated on TiO2 nanotubes through photoreduction of Pd ions, and its distribution is relatively homogeneous. From X-ray photoelectron spectrometry (XPS) result, the N 1 s spectrum represents two peaks with binding energy at 399.7 and 400.7 eV, which suggests that the nitrogen elements doped by hydrazine hydrate treatment are located in interstitial sites of the TiO2 crystalline structure. For N doped TiO2 nanotubes with Pd particles, a high photocurrent was detected due to increase of interface charge carrier separation rate. Moreover, N doped and Pd decorated TiO2 nanotubes exhibited much higher dye destruction efficiency and rate constant due to the synergistic effect of the N dopant and the Pd deposition on TiO2 nanotubes.